Two cases of hysterical aphonia - Isloor SD; Ramani G; Jagadish A (Journal of All India Institute of Speech and Hearing, 1970)
The term hysterical aphonia refers to a condition in which the patient looses the voice completely. The onset of the problem is sudden. There will not be any vocal pathology. The etiology will be psychological in nature. It is a conversion of psychological stress into sensory and motor dys-function. Here are the reports of two cases who came to our hospital with the complaint of no voice.